SOLUSI NUMERIK UNTUK PERSAMAAN INTEGRAL KUADRAT NONLINEAR - Eka Parmila Sari; Supriadi Putra; Agusni ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the existence and uniqueness of the solution, which was obtained using Adomian decomposition method, of a nonlinear quadratic integral equation. The discussion was continued by providing an analytical study of the convergence and the absolute error which are obtained by the solution found using Adomian decomposition method. The process of obtaining the solution of a nonlinear quadratic integral equation using Adomian decomposition method then expanded to the modiﬁed Adomian decomposition method. Comparison using numerical computation shows that the solution of quadratic nonlinear integral equationobtained using the modiﬁed Adomian decomposition method is better than those obtained by Adomian decomposition method.